Gender Inequality and Family Representation in The Film Andai Ibu Tidak Menikah Dengan Ayah - Chintawati, Reinnia; Syaifullah, Khalid; Sudrajat, Arief (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study examines the representation of gender inequality in the Indonesian film Andai Ibu Tidak Menikah dengan Ayah and the circulation of its meanings through audience discourse on TikTok. Using a qualitative approach grounded in Fairclough’s Critical Discourse Analysis, the study analyzes the relationship between the filmic text, selected audience comments, and the broader social structures in which these discourses operate. The data consist of eight key scenes from the film and relevant TikTok responses that address domestic labor, emotional responsibility, and parental roles. The findings show that the film positions the mother as the narrative center who bears overlapping domestic, economic, and emotional burdens, while the father is represented through absent or destructive forms of masculinity. These representations contribute to the naturalization of women’s double burden within patriarchal family structures. At the same time, digital audience discourse reveals forms of discursive negotiation and critique, particularly from women who relate personal experiences to the film and question the moralization of maternal endurance. This study demonstrates that film and digital media function simultaneously as sites for the reproduction and contestation of patriarchal ideology. It contributes to gender and media studies by situating gender performativity within Indonesian popular culture and participatory digital contexts.